Re-Os dating of paleozoic organic-rich black shales by LA-ICP-MS/MS - Jay M. Thompson; Stijn Glorie; A. Kate Souders; Sarah E. Gilbert; Timothy Paton; Poul Emsbo (Chemical Geology, 2026)

Tracing provenance and diagenetic history of Mesoproterozoic organic-rich shales from the McArthur Basin, Australia, using coupled Rb-Sr and K-Ar illite dating - Yaser Noorian; Juraj Farkaš; Alan S. Collins; Claudio Delle Piane; Andrew Todd; Sarah E. Gilbert; Rong Fan; Cecilia Loyola (Chemical Geology, 2026)

In-situ RbSr dating of the crystalline basement beneath the Amadeus Basin, Australia: Implications for the radiogenic helium generation, migration and extreme 4He accumulation - Cecilia Loyola; Juraj Farkaš; Alan S. Collins; Jason Alexander Charlwood; Sarah E. Gilbert; Peter W. Haines (Chemical Geology, 2026)

In situ Rb–Sr geochronology records multiple fluid pulses in Neoproterozoic sequences from the Lubambe-Mingomba Cu deposits in the Zambian Copperbelt - Victor Ikechukwu Vincent; Koen Torremans; Darwinaji Subarkah; Sarah E. Gilbert; Juraj Farkaš; Alan S. Collins; Jon Stacey; Aileen L. Doran; Simon Jones; Murray W. Hitzman (Precambrian Research, 2026)

Age of the Acraman impact ejecta layer in the adelaide superbasin and Implications on clay-mineral provenance from the Rb–Sr systematics of middle Ediacaran shales - Alan S. Collins; Morgan L. Blades; Darwinaji Subarkah; Holly Cooke; Lesley Edwards; Chelsea Forbister; Jake Jolly; Jarred C. Lloyd; Sarah E. Gilbert; Stefan Löhr; Juraj Farkaš; Victor Gostin (Precambrian Research, 2026)

Cumulative effects analysis to inform public land management in the United States: key characteristics and legal challenges - Tait K. Rutherford; Tim O. Hammond; Alison C. Foster; Megan A. Gilbert; Travis S. Haby; Richard J. Lehrter; Jennifer K. Meineke; Ella M. Samuel; Sarah K. Carter (Environmental Impact Assessment Review, 2026)

Spatially Modulated Irradiation Alters Extracellular Vesicle MicroRNA Cargo in Rat Glioma and Astrocyte Models - Sarah Potiron; Julie Espenon; Cristele Gilbert; Ahmed Glayl; Alfredo Fernandez-Rodriguez; Angela Corvino; Marjorie Juchaux; Yolanda Prezado (Molecular Neurobiology, 2026)
Spatially fractionated radiation therapy, particularly minibeam radiation therapy (MBRT), improves normal tissue sparing while maintaining tumor control compared with conventional radiotherapy (CRT). However, the mechanisms underlying these advantages remain unclear. EVs carrying miRNAs are increasingly recognized as mediators of radiation-induced intercellular communication and may contribute to non-targeted and cohort effects. We investigated the impact of MBRT versus CRT on EV-miRNA profiles in glioma and normal astrocyte cell lines. Rat glioma (RG2, F98) and astrocyte (CTX-TNA2) cell lines were irradiated with X-ray CRT or MBRT. Small EVs were isolated 24 h post-irradiation, characterized by transmission electron microscopy and nanoflow cytometry, and analyzed by small RNA sequencing. EV morphology, size, and expression of canonical markers (CD9, CD63, CD81) were preserved across conditions, indicating that irradiation primarily altered EV cargo. Glioma cells showed limited and cell-dependent changes. In RG2 cells, CRT increased miR-6319 and miR-374-5p, whereas MBRT modulated miR-151-5p in a dose-dependent manner and reduced miR-466c-5p at 5 Gy. No significant changes were observed in F98 cells. In contrast, astrocytes exhibited marked remodeling of EV-miRNA cargo after irradiation, including enrichment of miRNAs associated with stress adaptation, hypoxia-related signalling, and immune regulation, together with consistent depletion of miR-122b and miR-486 across irradiation conditions. MBRT and CRT were associated with differential remodeling of EV miRNA cargo, with a markedly stronger response in astrocytes than in glioma cells. These findings suggest altered EV signaling potential following irradiation and provide an initial molecular framework for investigating how spatial dose modulation may influence extracellular communication. Further functional validation in human-relevant systems is required to determine mechanistic and translational significance.

Geochronological and geochemical insights into episyenite metasomatic overprint in the Proterozoic Suomenniemi rapakivi granite complex (Finland) - Adam Abersteiner; O. Tapani Rämö; Alkis Kontonikas-Charos; Melissa Kharkongor; Nikolaos Karampelas; Sarah E. Gilbert; Ben Wade; Karolina Ambroziak-Murzyn; Jarred C. Lloyd; Christoph Beier; Stijn Glorie (Lithos, 2025)

The state and fate of noble metals in bornite and digenite - Samuel A. King; Cristiana L. Ciobanu; Nigel J. Cook; Ashley D. Slattery; Sarah E. Gilbert; J. Richard Kyle; Kathy Ehrig; Jie Yao (Lithos, 2025)

Volcanoes to vugs: Demonstrating a FAIR geochemistry framework with a diverse application of major and trace element data through the AuScope EarthBank platform - Angus L. Nixon; Samuel C. Boone; Yoann Gréau; Fabian Kohlmann; Moritz Theile; Wayne Noble; Alexander Prent; John Foden; Steven Barnes; Ashlea N. Wainwright; Benjamin Wade; Karsten Goemann; et al. (Chemical Geology, 2025)

Erratum to < Erratum to <“Dating of marine authigenic minerals via in situ Rb–Sr, U–Pb, and Lu–Hf: A case study from the Georgina Basin, Australia>< Chemical Geology 695 (2025) 123042> - Zhufu Shao; Juraj Farkaš; Stijn Glorie; Alan S. Collins; Sarah E. Gilbert; Darwinaji Subarkah (Chemical Geology, 2025)

In situ La Ba geochronology by LA-ICP-MS/MS: A new method to rapidly date LREE-rich minerals - Stijn Glorie; Sarah E. Gilbert (Chemical Geology, 2025)

Dating of marine authigenic minerals via in situ RbSr, UPb, and Lu–Hf: A case study from the Georgina Basin, Australia - Zhufu Shao; Juraj Farkaš; Stijn Glorie; Alan S. Collins; Sarah E. Gilbert; Darwinaji Subarkah (Chemical Geology, 2025)

Personality traits of aged dogs according to their cognitive status - Audrey Besegher; Sarah Jeannin; Nancy Rebout; Tiphaine Blanchard; Samanta Świerk; Yohan Stephan; Caroline Gilbert; Morgane Robles; Thierry Bedossa; Sara Hoummady (Applied Animal Behaviour Science, 2025)

Climate Consideration in Environmental Effects Analyses on Federal Public Lands in the United States - Sarah E. Whipple; Sarah K. Carter; Tait K. Rutherford; Samuel E. Jordan; Richard J. Lehrter; Christopher T. Domschke; Megan A. Gilbert; Julian Reyes; Ella M. Samuel; Karen M. Schank; John C. Tull; David J. A. Wood (Environmental Management, 2025)

In situ Rb–Sr dating and REE analysis of glauconites and detrital feldspars from the Ediacaran/Cambrian strata: Centralian and Adelaide Superbasins, Australia - Cecilia Loyola; Juraj Farkaš; Alan S. Collins; Sarah E. Gilbert; Charles Verdel; Stefan C. Löhr; Glenn A. Brock; Graham A. Shields; Andre Baldermann; Ahmad Redaa; Morgan Blades; Darwinaji Subarkah; et al. (Precambrian Research, 2025)

Apatite in situ Lu-Hf and U-Pb geochronology in layered mafic intrusions - Melissa Kharkongor; Stijn Glorie; Adam Abersteiner; Sarah Dare; Christopher Kirkland; David Chew; Jacob Mulder; Sarah Gilbert (Geochimica et Cosmochimica Acta, 2025)

A European survey on anaerobes from paediatric blood cultures: a comparative analysis with adults - Matteo Boattini; Arianna Aceti; Paulo Bastos; Viktoria Eirini Mavromanolaki; Sofia Maraki; Anastasia Spiliopoulou; Vasileios Kakouris; Yordan Kalchev; Ana Budimir; Branka Bedenić; Zana Rubic; Monica Licker; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Trace element distributions among Cu-(Fe)-sulfides from the Olympic Dam Cu-U-Au-Ag deposit, South Australia - Samuel A. King; Nigel J. Cook; Cristiana L. Ciobanu; Kathy Ehrig; Sarah Gilbert; Benjamin Wade; Yuri T. Campo Rodriguez (Mineralium Deposita, 2025)

Coupled Lu-Hf and U-Pb apatite geochronology of Jatobá orebody supports ∼ 2.5 Ga metamorphism in deep shear zones from southern Copper Belt, Carajás Domain, Brazil - Yuri Tatiana Campo-Rodriguez; Cristiana L. Ciobanu; Sarah Gilbert; Benjamin Wade; Nigel J. Cook; Maria Emilia Schutesky; Kathy Ehrig (Precambrian Research, 2025)

Monazite, lanthanide-rich glasses, and other trace elements in copper smelter slags: constraints on critical metal behaviour in Si-Fe-rich melts - Hassan Gezzaz; Cristiana L. Ciobanu; Nigel J. Cook; Kathy Ehrig; Ashley Slattery; Benjamin Wade; Sarah Gilbert; Yuri T. Campo Rodriguez (Mineralogy and Petrology, 2025)
Furnace slags are potential new sources of critical metals. We undertook a micron- to nanoscale study that addresses speciation, distribution and associations of phases in air-cooled flash furnace (FF, oxidised) and electric furnace (EF, reduced) slags from the Olympic Dam mining-smelting-refinery operation. Results enable understanding of the behaviour and partitioning of critical metals between melt and cooling crystalline phases in a controlled smelter environment that mimics Fe-Si-rich systems in Nature. Melts at ~ 1300 °C result in slags that differ in the relative proportions of component phases. Both FF and EF slags comprise major magnetite and two, compositionally distinct Si-Fe-rich glasses (glass-1 and -2); fayalite is a main component of EF slag. Glass-1 is rich in REE + Y (4.5–5.4 wt%, Ce 2 O 3 + La 2 O 3 ) and contains dendritic monazite-(Ce). Glass-2 (~ 70 wt% SiO 2 ) contains < 1 wt% Ce 2 O 3 + La 2 O 3 . The EF slag reaction sequence is: magnetite $$→$$ → fayalite + glass-1 $$→$$ → monazite $$→$$ → glass-2. Immiscibility of REE-rich liquid from Si-Fe-rich melt is inferred from amorphous ‘monazite-like’ droplets. Chondrite-normalised fractionation patterns are defined by downwards-sloping LREE segments in both glasses. Partition coefficients are calculated for magnetite and fayalite relative to glasses. D REY for HREE exceeds those for LREE in all phases and fayalite has an order of magnetite higher D HREE than co-existing EF magnetite. Applying lattice strain models to experimental values show excellent fits for D HREE-model trends, even if lattice strain is not the sole factor controlling partitioning. Melt polymerisation, variable/unpredictable oxidation states, and constraints from specific crystallographic sites, also impact on observed trends. This study provides clues to element behaviour in metallurgical plants that can assist potential utilization of copper smelter slags to meet the demand for REE and other contained critical metals.

Effects of temperature and nutrient load on the interaction of Vibrio parahaemolyticus and plastic pollution in the marine environment - Kara J. Wiggin; Ryan K. Chung; Jack A. Gilbert; Sarah M. Allard (Marine Pollution Bulletin, 2025)

Historical genomic variation of Eurasian otters (Lutra lutra) in Britain, from hunting trophies - Sarah J. du Plessis; Nuno F. Martins; Xin Sun; Sarah S. T. Mak; David W. G. Stanton; Klaus-Peter Koepfli; Elizabeth A. Chadwick; M. P. Thomas Gilbert; Frank Hailer (Conservation Genetics Resources, 2025)
Genomic data from historical specimens can provide insights into populations and processes no longer evident from modern samples. Identifying viable sources of historical DNA is key to this. Here we aimed to explore the viability of trophy hunting paws as sources of historical DNA, and to use this data for preliminary analyses to evaluate changes in population structuring over time. We aimed to search for the presence of genomic signals of the putative recent introduction of Eurasian otters ( Lutra lutra ) from Asia to the UK previously identified using modern data, by analysis of two trophy paws from 1929 to 1952. Substantial proportions of endogenous DNA (77–85%) were identified in both samples for which genomic DNA extraction and sequencing was attempted, illustrating the potential of such specimens for historical DNA research. Autosomal variation suggests that the historical specimens cluster closest to modern specimens from Wales, and not with the variation identified in the East of England, putatively associated with the recent introduction of Eurasian otters from Asia. Similarly, the divergent mitochondrial lineage found in modern otters from the East of England and Asia, was not found in the historical British specimens. Although limited inferences can be made from a sample size of two, this preliminary dataset indicates the huge potential of historical trophy paw samples to assess past population genetic dynamics, calling for further research in this area.

Identifying Priority Science Information Needs for Managing Public Lands - Sarah K. Carter; Travis S. Haby; Ella M. Samuel; Alison C. Foster; Jennifer K. Meineke; Laine E. McCall; Malia K. Burton; Christopher T. Domschke; Leigh D. Espy; Megan A. Gilbert (Environmental Management, 2025)

A holo-omics analysis shows how sugar kelp can boost gut health in Atlantic salmon - Jacob A. Rasmussen; Annette Bernhard; Laurène A. Lecaudey; Varsha Kale; Germana Baldi; Lene S. Myrmel; Martin Hansen; Jaelle C. Brealey; Sarah S.T. Mak; Ida B. Nielsen; Lorna Richardson; Lise Madsen; et al. (Aquaculture, 2025)

Mineralogy, mineral chemistry, and genesis of Cu-Ni-As-rich ores at Lisheen, Ireland - Max Frenzel; Markus Röhner; Nigel J. Cook; Sarah Gilbert; Cristiana L. Ciobanu; John F. Güven (Mineralium Deposita, 2025)
The Irish Orefield is characterised by the presence of both Zn-Pb- and Cu-Ni-As-rich deposits, prospects, and orebodies in similar structural and stratigraphic positions. However, the genetic relationships between these mineralisation types are still debated. In this article, we present new mineralogical, paragenetic, and mineral-chemical observations from the Cu-Ni-As-rich ores at the classic Lisheen deposit, County Tipperary. These observations indicate the intimate association and cogenetic nature of these ores with the more abundant Zn-Pb-rich mineralisation. Specifically, both mineralisation types appear to have formed at the same time, under similar physicochemical conditions, and from the same ore fluids. In addition, both types of mineralisation contain elevated Ge contents. The cogenetic nature of the two mineralisation types, the relative absence of Cu-Ni-As-rich ores from most of the larger Irish-type Zn-Pb deposits compared to expectations derived from probable ore fluid compositions, and finally, the known geological characteristics of larger Cu-Ni-As-rich ore bodies, like Gortdrum, indicate that significant Cu-Ni-As-rich mineralisation could be present at lower stratigraphic levels across the Irish Orefield. Areas with extensive known Zn-Pb mineralisation are expected to be particularly prospective for such ores, which may occur at stratigraphic levels as deep as the Old Red Sandstone. This may have additional implications beyond Ireland, and could point to the potential for undiscovered Cu-rich ores in low-temperature carbonate-hosted Zn-Pb districts elsewhere.

LA-ICP-Q-MS/MS ReOs geochronology: A comparison of N2O and CH4 reaction gases - Alexander Simpson; Stijn Glorie; Sarah Gilbert; Renée Tamblyn; Michael G. Gadd (Chemical Geology, 2024)

Vaccination of endangered wildlife as a conservation tool: Hindsights and new horizons in the pandemic era - Frances M.D. Gulland; Michelle Barbieri; Sarah Cleaveland; Martin Gilbert; Ailsa J. Hall; Tonie E. Rocke (Biological Conservation, 2024)

Using zircon and apatite chemistry to fingerprint porphyry Cu – Mo ± Au mineralization in the Delamerian Orogen, South Australia - Wei Hong; Adrian Fabris; Sarah Gilbert; Benjamin P. Wade; Alan S. Collins; Tom Wise; Anthony J. Reid (Mineralium Deposita, 2024)
To evaluate the fertility of porphyry mineralization in the Delamerian Orogen (South Australia), zircon and apatite from four prospects, including Anabama Hill, Netley Hill, Bendigo, and Colebatch, have been analyzed by LA-ICP-MS and electron microprobe. The zircon is characterized by heavy REEs enrichment relative to light REEs, high (Ce/Nd) N (1.3–45), and weak to moderate negative Eu/Eu* (0.2–0.78). The apatite has right-sloped REE patterns with variably negative to positive Eu anomalies. Low Mg (< 670 ppm) and Sr/Y ratios (< 5) in apatite likely illustrate fractional crystallization trends for the granitic melts in shallow crust. The Yb/Gb and Eu/Eu* in zircon reveal that intrusions at Anabama Hill, Netley Hill, and Bendigo underwent fractional crystallization controlled by amphibole (< 50–60%), garnet (< 15%), apatite (< 0.6%), and/or titanite (< 0.3%). These stocks have average f O 2 values reported relative to fayalite-magnetite-quartz buffer (ΔFMQ), from 0.7 ± 0.9 to 2.1 ± 0.4, ascribed to prolonged magmatic evolution or sulfur degassing during post-subduction processes. Our data imply that both Anabama and Bendigo complexes experienced prevalent (garnet-) amphibole crystallization from hydrous melts that have moderately high oxidation (ΔFMQ + 1 to + 3) and elevated sulfur-chlorine components (Anabama, 37 ± 9 to 134 ± 83 ppm S and 0.30 ± 0.24 to 0.64 ± 0.89 wt% Cl; Bendigo, 281 ± 178 to 909 ± 474 ppm S and 0.45 ± 0.47 to 3.01 ± 1.54 wt% Cl). These are crucial ingredients to form porphyry Cu–Mo ± Au ores with economic significance, which provides encouragement for mineral exploration in this orogen.

Double dating sedimentary sequences using new applications of in-situ laser ablation analysis - Darwinaji Subarkah; Angus L. Nixon; Sarah E. Gilbert; Alan S. Collins; Morgan L. Blades; Alexander Simpson; Jarred C. Lloyd; Georgina M. Virgo; Juraj Farkaš (Lithos, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Laser ablation (in situ) Lu-Hf geochronology of epidote group minerals - Jie Yu; Stijn Glorie; Martin Hand; Alexander Simpson; Sarah Gilbert; Kristoffer Szilas; Nick Roberts; Mark Pawley; Yanbo Cheng (Contributions to Mineralogy and Petrology, 2024)
Epidote group minerals, including allanite, clinozoisite and epidote are common in a range of metamorphic, igneous and hydrothermal systems, and are stable across a wide range of pressure – temperature ( P–T ) conditions. These minerals can incorporate substantial amounts of rare earth elements (REEs) during their crystallisation, making them potential candidates for Lu–Hf geochronology to provide age constraints on various geological processes. Here we report on a first exploration into the feasibility of in situ Lu–Hf geochronology for epidote group minerals from various geological settings and compare the results with age constraints from other geochronometers. Magmatic allanite samples from pegmatites and monzogranites in the Greenland anorthosite complex, Coompana Province and Qingling Orogen provided dates consistent with magmatic events spanning from c. 2660 to 1171 Ma. In the Qingling pegmatites, a younger phase of hydrothermal allanite was dated at c. 215 Ma, consistent with the timing of regional REE mineralisation. Allanite from the Yambah Shear Zone, Strangways Metamorphic Complex, yielded Lu–Hf age of c. 430 Ma. It predates the garnet and apatite growth at c. 380 Ma, suggesting the Lu–Hf system can be preserved in allanite during prograde amphibolite-facies metamorphism. Additionally, Lu–Hf dates for hydrothermal clinozoisite and epidote are consistent with the timing of hydrothermal alteration and mineralisation in a range of settings, demonstrating the utility of the technique for mineral exploration. Despite the current lack of matrix-matched reference materials, the successful application of laser ablation Lu–Hf geochronology to epidote group minerals offers valuable geochronological insights into various geological processes that can be difficult to access through other geochronometers.

Trace element impurities in anode copper from Olympic Dam, South Australia - Nigel J. Cook; Kathy Ehrig; Cristiana L. Ciobanu; Sarah E. Gilbert; Hassan Gezzaz (Minerals Engineering, 2024)

Testing the reproducibility of in situ Lu Hf dating using Lu-rich garnet from the Tørdal pegmatites, southern Norway - Stijn Glorie; Alexander Simpson; Sarah E. Gilbert; Martin Hand; Axel B. Müller (Chemical Geology, 2024)

Development of a culturally targeted chatbot to inform living kidney donor candidates of African ancestry about APOL1 genetic testing: a mixed methods study - Elisa J. Gordon; Jessica Gacki-Smith; Matthew J. Gooden; Preeya Waite; Rochell Yacat; Zenab R. Abubakari; Debra Duquette; Akansha Agrawal; John Friedewald; Sarah K. Savage; Matthew Cooper; Alexander Gilbert; et al. (Journal of Community Genetics, 2024)
Clinical chatbots are increasingly used to help integrate genetic testing into clinical contexts, but no chatbot exists for A polipoprotein L1 ( APOL1 ) genetic testing of living kidney donor (LKD) candidates of African ancestry. Our study aimed to culturally adapt and assess perceptions of the Gia® chatbot to help integrate APOL1 testing into LKD evaluation. Ten focus groups and post-focus group surveys were conducted with 54 LKDs, community members, and kidney transplant recipients of African ancestry. Data were analyzed through thematic analysis and descriptive statistics. Key themes about making Gia culturally targeted included ensuring: (1) transparency by providing Black LKDs’ testimonials, explaining patient privacy and confidentiality protections, and explaining how genetic testing can help LKD evaluation; (2) content is informative by educating Black LKDs about APOL1 testing instead of aiming to convince them to undergo testing, presenting statistics, and describing how genetic discrimination is legally prevented; and (3) content avoids stigma about living donation in the Black community. Most agreed Gia was neutral and unbiased (82%), trustworthy (82%), and words, phrases, and expressions were familiar to the intended audience (85%). Our culturally adapted APOL1 Gia chatbot was well regarded. Future research should assess how this chatbot could supplement provider discussion prior to genetic testing to scale APOL1 counseling and testing for LKD candidate clinical evaluation.

Exploring the microbial diversity of novel misos with metagenomics - Caroline Isabel Kothe; Jacob Agerbo Rasmussen; Sarah S.T. Mak; M. Thomas P. Gilbert; Joshua Evans (Food Microbiology, 2024)

Implications for metallogenic evolution of the giant Zhenyuan gold deposit (Yunnan, SW China) from textures and geochemical compositions of pyrite - Huichao Zhang; Nigel J. Cook; Hongrui Zhang; Zengqian Hou; Peng Chai; Wei Li; Sarah Gilbert (Contributions to Mineralogy and Petrology, 2024)

Rare earth element and yttrium (REY) geochemistry of 3.46–2.45 Ga greenalite-bearing banded iron formations: New insights into iron deposition and ancient ocean chemistry - Janet R. Muhling; Sarah E. Gilbert; Birger Rasmussen (Chemical Geology, 2023)

Garnet Lu-Hf speed dating: A novel method to rapidly resolve polymetamorphic histories - Alexander Simpson; Stijn Glorie; Martin Hand; Carl Spandler; Sarah Gilbert (Gondwana Research, 2023)

Biotic and Abiotic Control Over Diurnal CH4 Fluxes in a Temperate Transitional Poor Fen Ecosystem - Alexandre Lhosmot; Adrien Jacotot; Marc Steinmann; Philippe Binet; Marie-Laure Toussaint; Sébastien Gogo; Daniel Gilbert; Sarah Coffinet; Fatima Laggoun-Deffarge; Guillaume Bertrand (Ecosystems, 2023)

Mineralogical, magnetic and geochemical data constrain the pathways and extent of weathering of mineralized sedimentary rocks - Sergio Carrero; Sarah P. Slotznick; Sirine C. Fakra; M. Cole Sitar; Sharon E. Bone; Jeffrey L. Mauk; Andrew H. Manning; Nicholas L. Swanson-Hysell; Kenneth H Williams; Jillian F. Banfield; Benjamin Gilbert (Geochimica et Cosmochimica Acta, 2023)

How does co-produced research influence adaptive capacity? Lessons from a cross-case comparison - Sarah P. Church; Chloe B. Wardropper; Emily Usher; Liam F. Bean; Ashlie Gilbert; Francis R. Eanes; Jessica D. Ulrich-Schad; Nicholas Babin; Pranay Ranjan; Jackie M. Getson; Laura A. Esman; Linda S. Prokopy (Socio-Ecological Practice Research, 2022)

Correction to: Tracking the history of grapevine cultivation in Georgia by combining geometric morphometrics and ancient DNA - Laurent Bouby; Nathan Wales; Mindia Jalabadze; Nana Rusishvili; Vincent Bonhomme; Jazmín Ramos‑Madrigal; Allowen Evin; Sarah Ivorra; Thierry Lacombe; Clémence Pagnoux; Elisabetta Boaretto; M. Thomas P. Gilbert; et al. (Vegetation History and Archaeobotany, 2022)

Ecological consequences of large herbivore exclusion in an A frican savanna: 12 years of data from the UHURU experiment - Jesse M. Alston; Courtney G. Reed; Leo M. Khasoha; Bianca R. P. Brown; Gilbert Busienei; Nathaniel Carlson; Tyler C. Coverdale; Megan Dudenhoeffer; Marissa A. Dyck; John Ekeno; Abdikadir A. Hassan; Rhianna Hohbein; et al. (Ecology, 2022)
Diverse communities of large mammalian herbivores (LMH), once widespread, are now rare. LMH exert strong direct and indirect effects on community structure and ecosystem functions, and measuring these effects is important for testing ecological theory and for understanding past, current, and future environmental change. This in turn requires long‐term experimental manipulations, owing to the slow and often nonlinear responses of populations and assemblages to LMH removal. Moreover, the effects of particular species or body‐size classes within diverse LMH guilds are difficult to pinpoint, and the magnitude and even direction of these effects often depends on environmental context. Since 2008, we have maintained the Ungulate Herbivory Under Rainfall Uncertainty (UHURU) experiment, a series of size‐selective LMH exclosures replicated across a rainfall/productivity gradient in a semiarid Kenyan savanna. The goals of the UHURU experiment are to measure the effects of removing successively smaller size classes of LMH (mimicking the process of size‐biased extirpation) and to establish how these effects are shaped by spatial and temporal variation in rainfall. The UHURU experiment comprises three LMH‐exclusion treatments and an unfenced control, applied to nine randomized blocks of contiguous 1‐ha plots ( n = 36). The fenced treatments are MEGA (exclusion of megaherbivores, elephant and giraffe), MESO (exclusion of herbivores ≥40 kg), and TOTAL (exclusion of herbivores ≥5 kg). Each block is replicated three times at three sites across the 20‐km rainfall gradient, which has fluctuated over the course of the experiment. The first 5 years of data were published previously ( Ecological Archives E095‐064) and have been used in numerous studies. Since that publication, we have (1) continued to collect data following the original protocols, (2) improved the taxonomic resolution and accuracy of plant and small‐mammal identifications, and (3) begun collecting several new data sets. Here, we present updated and extended raw data from the first 12 years of the UHURU experiment (2008–2019). Data include daily rainfall data throughout the experiment; annual surveys of understory plant communities; annual censuses of woody‐plant communities; annual measurements of individually tagged woody plants; monthly monitoring of flowering and fruiting phenology; every‐other‐month small‐mammal mark–recapture data; and quarterly large‐mammal dung surveys. There are no copyright restrictions; notification of when and how data are used is appreciated and users of UHURU data should cite this data paper when using the data.

Evolution of a hydrothermal ore-forming system recorded by sulfide mineral chemistry: a case study from the Plaka Pb–Zn–Ag Deposit, Lavrion, Greece - Max Frenzel; Panagiotis Voudouris; Nigel J. Cook; Cristiana L. Ciobanu; Sarah Gilbert; Benjamin P. Wade (Mineralium Deposita, 2022)
Laser ablation-inductively coupled plasma-mass spectrometry and electron-probe microanalysis were used to investigate the trace-element contents of sphalerite, chalcopyrite and pyrite from the Plaka Pb–Zn–Ag deposit. Using petrographic observations, the analytical results could be linked to the temporal evolution of the Plaka ore-forming system. Sphalerite chemistry reliably records the temperature and f S 2 evolution of the system, with estimated formation temperatures reproducing the microthermometric results from previous fluid-inclusion studies. Chalcopyrite chemistry also shows systematic variations over time, particularly for Cd, Co, Ge, In, Sn and Zn concentrations. Measurable pyrite was only found in association with early high-temperature mineralisation, and no clear trends could therefore be identified. We note, however, that As and Se contents in pyrite are consistent with formation temperatures estimated from co-existing sphalerite. Statistical analysis of the sphalerite data allowed us to identify the dominant geological controls on its trace-element content. The three investigated factors temperature, f S 2 , and sample location account for > 80% of the observed variance in Mn, Fe, Co, Ga, Ge, In, Sb and Hg concentrations, and > 60% of the observed variance in Cd and Sn concentrations. Only for Cu and Ag concentrations is the explained variance < 50%. A similarly detailed analysis was not possible for chalcopyrite and pyrite. Nevertheless, comparison of the results for all three investigated minerals indicates that there are some systematic variations across the deposit which may be explained by local differences in fluid composition.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Indium distribution in sphalerite from sulfide–oxide–silicate skarn assemblages: a case study of the Dulong Zn–Sn–In deposit, Southwest China - Jing Xu; Nigel J. Cook; Cristiana L. Ciobanu; Xiaofeng Li; Alkiviadis Kontonikas-Charos; Sarah Gilbert; Youhu Lv (Mineralium Deposita, 2021)

Tracking the history of grapevine cultivation in Georgia by combining geometric morphometrics and ancient DNA - Laurent Bouby; Nathan Wales; Mindia Jalabadze; Nana Rusishvili; Vincent Bonhomme; Jazmín Ramos-Madrigal; Allowen Evin; Sarah Ivorra; Thierry Lacombe; Clémence Pagnoux; Elisabetta Boaretto; M. Thomas P. Gilbert; et al. (Vegetation History and Archaeobotany, 2021)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

The use of 3 selected lactobacillary strains in vaginal probiotic gel for the treatment of acute Candida vaginitis: a proof-of-concept study - Gilbert Donders; Gert Bellen; Eline Oerlemans; Ingmar Claes; Kateryna Ruban; Tim Henkens; Filip Kiekens; Sarah Lebeer (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Coronavirus surveillance of wildlife in the Lao People’s Democratic Republic detects viral RNA in rodents - David J. McIver; Soubanh Silithammavong; Watthana Theppangna; Amethyst Gillis; Bounlom Douangngeun; Kongsy Khammavong; Sinpakone Singhalath; Veasna Duong; Philippe Buchy; Sarah H. Olson; Lucy Keatts; Amanda E. Fine; et al. (Archives of Virology, 2020)

Host-specific and tissue-dependent orchestration of microbiome community structure in traditional rice paddy ecosystems - Weijuan Huang; Sarah Gilbert; Alexander Poulev; Kenneth Acosta; Sarah Lebeis; Chunlin Long; Eric Lam (Plant and Soil, 2020)
Background and aim Rice and duckweed are two monocotyledonous plants that naturally coexist in paddy fields. While the presence of duckweed in paddy fields significantly improves rice productivity, the interplay between soil microbes and the two plant hosts in this agroecosystem remains unexplored. Methods We compared the bacterial community structure between duckweed, rice and soil from multiple rice paddies. We also isolated bacteria from these communities and characterized their modes of bacterial colonization and plant growth-promotion using model plants. Results Our data indicate that host-specific and tissue-dependent factors reproducibly orchestrate the bacterial community structure associated with their plant hosts. This is corroborated by results from culture-dependent approaches in which the dominant genus Pantoea isolated from rice aerial tissues can strongly attach and colonize gnotobiotic duckweed in spite of the low representation of this bacterial genus in the natural duckweed microbiome. Our study identified a core of 254 bacterial taxa that are consistently found in all rice and duckweed tissue samples from rice paddy fields. Furthermore, characterizing auxin-producing bacteria isolates from both plant species identified potential plant growth-promoting bacteria that may improve growth for both duckweed and rice in paddy fields. Conclusions Results from this work provide evidence for the importance of the host tissue and species context in determining plant colonization by microbes in the paddy field system. The resources generated in this study could facilitate the agronomic deployment of microbes for more sustainable rice production.

Erratum to: Cu–Ni–PGE fertility of the Yoko-Dovyren layered massif (northern Transbaikalia, Russia): thermodynamic modeling of sulfide compositions in low mineralized dunite based on quantitative sulfide mineralogy - Alexey A. Ariskin; Evgeny V. Kislov; Leonid V. Danyushevsky; Georgy S. Nikolaev; Marco L. Fiorentini; Sarah Gilbert; Karsten Goemann; Alexey Malyshev (Mineralium Deposita, 2018)

CCL11 (Eotaxin-1) Levels Predict Long-Term Functional Outcomes in Patients Following Ischemic Stroke - Meaghan Roy-O’Reilly; Rodney M. Ritzel; Sarah E. Conway; Ilene Staff; Gilbert Fortunato; Louise D. McCullough (Translational Stroke Research, 2017)

Baseline results from the UK SIGNIFY study: a whole-body MRI screening study in TP53 mutation carriers and matched controls - Sibel Saya; Emma Killick; Sarah Thomas; Natalie Taylor; Elizabeth K. Bancroft; Jeanette Rothwell; Sarah Benafif; Alexander Dias; Christos Mikropoulos; Jenny Pope; Anthony Chamberlain; Ranga Gunapala; et al. (Familial Cancer, 2017)

Cu–Ni–PGE fertility of the Yoko-Dovyren layered massif (northern Transbaikalia, Russia): thermodynamic modeling of sulfide compositions in low mineralized dunite based on quantitative sulfide mineralogy - Alexey A. Ariskin; Evgeny V. Kislov; Leonid V. Danyushevsky; Georgy S. Nikolaev; Marco L. Fiorentini; Sarah Gilbert; Karsten Goemann; Alexey Malyshev (Mineralium Deposita, 2016)

Spatial scale drives patterns in soil bacterial diversity - Sarah L. O'Brien; Sean M. Gibbons; Sarah M. Owens; Jarrad Hampton‐Marcell; Eric R. Johnston; Julie D. Jastrow; Jack A. Gilbert; Folker Meyer; Dionysios A. Antonopoulos (Environmental Microbiology, 2016)
Summary Soil microbial communities are essential for ecosystem function, but linking community composition to biogeochemical processes is challenging because of high microbial diversity and large spatial variability of most soil characteristics. We investigated soil bacterial community structure in a switchgrass stand planted on soil with a history of grassland vegetation at high spatial resolution to determine whether biogeographic trends occurred at the centimeter scale. Moreover, we tested whether such heterogeneity, if present, influenced community structure within or among ecosystems. Pronounced heterogeneity was observed at centimeter scales, with abrupt changes in relative abundance of phyla from sample to sample. At the ecosystem scale (> 10 m), however, bacterial community composition and structure were subtly, but significantly, altered by fertilization, with higher alpha diversity in fertilized plots. Moreover, by comparing these data with data from 1772 soils from the Earth Microbiome Project, it was found that 20% of bacterial taxa were shared between their site and diverse globally sourced soil samples, while grassland soils shared approximately 40% of their operational taxonomic units with the current study. By spanning several orders of magnitude, the analysis suggested that extreme patchiness characterized community structure at smaller scales but that coherent patterns emerged at larger length scales.

Neurodevelopmental Malformations of the Cerebellar Vermis in Genetically Engineered Rats - Raddy L. Ramos; Sarah E. Van Dine; Mary E. Gilbert; Joerg R. Leheste; German Torres (The Cerebellum, 2015)

Associations of vitamin D pathway genes with circulating 25-hydroxyvitamin-D, 1,25-dihydroxyvitamin-D, and prostate cancer: a nested case–control study - Rebecca Gilbert; Carolina Bonilla; Chris Metcalfe; Sarah Lewis; David M. Evans; William D. Fraser; John P. Kemp; Jenny L. Donovan; Freddie C. Hamdy; David E. Neal; J. Athene Lane; George Davey Smith; et al. (Cancer Causes & Control, 2015)

Transcriptomic profiling facilitates classification of response to influenza challenge - Emma E. Davenport; Richard D. Antrobus; Patrick J. Lillie; Sarah Gilbert; Julian C. Knight (Journal of Molecular Medicine, 2015)

Genome-wide association study and meta-analysis of intraocular pressure - A. Bilge Ozel; Sayoko E. Moroi; David M. Reed; Melisa Nika; Caroline M. Schmidt; Sara Akbari; Kathleen Scott; Frank Rozsa; Hemant Pawar; David C. Musch; Paul R. Lichter; Doug Gaasterland; et al. (Human Genetics, 2014)

Spatial relationships between lead sources and children’s blood lead levels in the urban center of Indianapolis (USA) - Deborah Morrison; Qing Lin; Sarah Wiehe; Gilbert Liu; Marc Rosenman; Trevor Fuller; Jane Wang; Gabriel Filippelli (Environmental Geochemistry and Health, 2013)

Multivariate Analysis of an LA-ICP-MS Trace Element Dataset for Pyrite - Lyron Winderbaum; Cristiana L. Ciobanu; Nigel J. Cook; Matthew Paul; Andrew Metcalfe; Sarah Gilbert (Mathematical Geosciences, 2012)

Predictors of 25-hydroxyvitamin D and its association with risk factors for prostate cancer: evidence from the Prostate testing for cancer and Treatment study - Rebecca Gilbert; Richard M. Martin; William D. Fraser; Sarah Lewis; Jenny Donovan; Freddie Hamdy; David E. Neal; J. Athene Lane; Chris Metcalfe (Cancer Causes & Control, 2012)

Genetic population structure and distribution of a fungal polypore, Datronia caperata (Polyporaceae), in mangrove forests of Central America - Sarah E. Bergemann; M. A. Smith; Jeri L. Parrent; Gregory S. Gilbert; Matteo Garbelotto (Journal of Biogeography, 2009)
Aim We examine the genetic structure of a fungal polypore, Datronia caperata (Berk.) Ryvarden (Polyporaceae), colonizing white mangrove, Laguncularia racemosa (L.) Gaertn. f. (Combretaceae), of Central America. Location Mangrove forests of Costa Rica and Panama. Methods Sequences of elongation factor alpha (EFA), beta tubulin (BTUB) and nuclear ribosomal internal transcribed spacer (ITS) regions were obtained from 54 collections of D . caperata collected from Caribbean and Pacific L. racemosa forests in Central America. Measures of haplotype and nucleotide diversity, nested clade analyses and coalescent analyses were used to estimate the direction and extent of migration of the fungus, and the factors promoting population divergence. We also conducted phylogenetic analyses using Bayesian estimation to test whether putative D. caperata collected from L. racemosa was conspecific with D. caperata colonizing other hosts from diverse Neotropical forests. Results Our results demonstrate that there is genetic isolation between D. caperata populations from Caribbean mangroves and those from Pacific mangroves. Our data suggest that the best explanation for the observed haplotype distribution is a recent range expansion from the Caribbean to the Pacific coasts, with subsequent isolation. This is supported by the infrequent overlap of haplotypes, unidirectional migration estimates from the Caribbean to the Pacific and the older estimated age of mutations in the Caribbean low‐copy BTUB and EFA loci. In addition, our data suggest that D. caperata from mangroves are not conspecific with collections from other hosts found in diverse Neotropical forests. Main conclusions The low frequency of shared haplotypes between coasts, coupled with the incomplete lineage sorting after cessation of gene flow, is consistent with isolation during the last Pleistocene glaciation. We hypothesize that the greater haplotype and nucleotide diversity in the Pacific occurs either because larger effective population sizes of D. caperata are maintained in Pacific mangroves or because D . caperata populations underwent a significant bottleneck as a result of local extinction followed by recolonization. In addition, we found that D. caperata found on L. racemosa was not conspecific with D. caperata from non‐mangrove hosts and suggest that D. caperata found on L. racemosa may be a host specialist.

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

The Record of an Extreme Flood in the Sediments of Montane Lillooet Lake, British Columbia: Implications for Paleoenvironmental Assessment - Robert Gilbert; Sarah Crookshanks; Kyle R. Hodder; John Spagnol; Roland B. Stull (Journal of Paleolimnology, 2006)

Mating Behavior, Sexual Selection, and Copulatory Courtship in a Promiscuous Beetle - David Shuker; Nick Bateson; Heidi Breitsprecher; Rebecca O'Donovan; Helen Taylor; Chris Barnard; Jerzy Behnke; Sarah Collins; Francis Gilbert (Journal of Insect Behavior, 2002)

Mutational analysis of the GDNF/RET-GDNFRα signaling complex in a kindred with vesicoureteral reflux - Sarah E. Shefelbine; Sangeeta Khorana; Pamela N. Schultz; Eileen Huang; Nicole Thobe; Zheng J. Hu; Gary M. Fox; Shuqian Jing; Gilbert J. Cote; R. F. Gagel (Human Genetics, 1998)